2021
DOI: 10.1021/acsnano.1c07252
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Transport Pathways Guided by Grain Architectures in Ni-Rich Layered Cathodes

Abstract: Ni-rich layered cathodes have been used in commercial Li-ion batteries because of their high capacity and low cost. However, they suffer from crack formation at the grain boundaries owing to heterogeneous large volume changes during the reactions. To improve their performance, a comprehensive understanding of the grain architecture, Li transport pathways, and phase transitions is essential. Here, we show the correlations between these factors using in situ transmission electron microscopy. The results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
1
27
1
Order By: Relevance
“…The results indicated that the Li-ion migration occurred as bulk diffusion rather than along the grain boundaries. The difference in the Li-ion diffusion rate was found to depend on the degree of mismatch between the orientation of adjacent crystals, which is completely different from previously reported information (Figure 7(e, f)) [203,204].…”
Section: Particles With Intracrystalline Defectscontrasting
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the Li-ion migration occurred as bulk diffusion rather than along the grain boundaries. The difference in the Li-ion diffusion rate was found to depend on the degree of mismatch between the orientation of adjacent crystals, which is completely different from previously reported information (Figure 7(e, f)) [203,204].…”
Section: Particles With Intracrystalline Defectscontrasting
confidence: 99%
“…The creation of twin boundaries and antiphase boundaries during the Li-ion extraction in LCO was also observed by Yang et al (Figure 7(b, c)) [200]. Moreover, using HR-STEM, Tan et al during the charge reaction and subsequent relaxation [204]. Copyright 2021, American Chemical Society.…”
Section: Particles With Intracrystalline Defectsmentioning
confidence: 53%
“…Closer observation of the peak profiles of reflections at the beginning of discharge (Figure b) shows there is some broadening at high states of charge, particularly as the Li content progresses from 0.138 < x (Li) < 0.25. This may be related to phase segregation within the cathode material into Li-rich and Li-poor phases at high states of delithiation and at high current densities as a result of different Li diffusivity between the two phases. This behavior has been previously observed in various Ni-rich materials with Ni content as low as y = 0.6 and thus could be expected to occur in all of the materials presented here …”
Section: Resultssupporting
confidence: 53%
“…The materials with excellent rate capability facilitate Li + diffusion due to its reversible migration and redox behavior of Ni and Co. Using insitu STEM combined with electron energy loss spectroscopy (EELS) and crystal orientation mapping, Nomura et al [90] determined Li + transport paths and phase separation in polycrystalline NCA cathode (Figure 6c). Through this method, changes in Li distribution under operating conditions are observed.…”
Section: Theoretical and Experimental Research Techniquesmentioning
confidence: 99%
“…c) ADF-STEM image around an NCA secondary particle, change in Li distribution during the charge reaction and subsequent relaxation, and crystal orientation map. Reprinted with permission from ref [90]…”
mentioning
confidence: 99%